Effect of adenosine on the expression of β2 integrins and L-selectin of human polymorphonuclear leukocytes in vitro - Thiel, Manfred; Chambers, J David; Chouker, A; Fischer, S; Zourelidis, C; Bardenheuer, Hubert J.; Arfors, Karl-E; Peter, K (Journal of leukocyte biology, 1996)
Adenosine has been shown to inhibit the adhesion of polymorphonuclear leukocytes (PMNL) to the vascular endothelium. Because the underlying molecular mechanisms have not been fully understood, the present study characterizes the effect of adenosine on the expression of adhesion molecules of human PMNL. When PMNL were activated by N-formyl-methionyl-leucyl-phenylalanine the number of cell surface β2 integrins increased fivefold, whereas L-selectin molecules were completely shed. Activation-dependent numerical up-regulation of β2 integrins and shedding of L-selectin were inhibited by exogenously applied adenosine receptor agonists in a concentration-dependent fashion. The rank or-der of potencies of adenosine receptor agonists, measured by the agonists’ half-maximal inhibitory concentrations, revealed that adenosine inhibited the numerical up-regulation of β2 integrins and shedding of L-selectin most likely via an A2(a) receptor site. When extracellular concentrations of endogenously formed adenosine were enhanced by the nucleoside uptake inhibitor dipyridamole, up-regulation of β2 integrins, and shedding of L-selectin was again inhibited. Both effects were reversed by the enzyme adenosine deaminase, which degrades active adenosine to inactive inosine, suggesting that endogenously formed adenosine may play an important role in the regulation of β2 integrins and L-selectin of human PMNL.